Pengambilan Keputusan Dalam Menentukan Media Pembelajaran Online Pada Masa Pandemi Menggunakan Metode AHP dan TOPSIS - Syahyulita Fachri; Eka Irawan; Ilham Syahputra Saragih (BEES: Bulletin of Electrical and Electronics Engineering, 2021)
STIKOM Tunas Bangsa is one of the computer science colleges located in Pematangsiantar City. Due to the Covid-19 Pandemic Period, the teaching and learning process is carried out online at their respective homes by students and lecturers. Sources of data obtained by interview and direct observation to students. The author's goal in this study is to determine the best learning media in the Information Systems Study Program at STIKOM Tunas Bangsa by using a combination of TOPSIS and AHP methods. With the given material variables, What'sApp variables, Classroom variables, and E-Learning variables, Google Meet variables and Zoom variables. The result of this study is the increase in the learning process and understanding of students during the Covid 19 Pandemic